Development of a mixer free doppler ultrasound fetal monitor - Al-Badri, Mohammed (2021)
Fetal Heart Rate (FHR) monitoring using Doppler Ultrasound (DUS) is a noninvasive technique that is in widespread use to assess fetal well-being both during pregnancy (antepartum) and labour (intrapartum) However, despite the routine use of FHR monitoring for several decades, the DUS method can under certain conditions provides estimates of FHR of insufficient accuracy. Well-known problems are doubling of the FHR and calculating the FHR from signals arising from maternal blood flow.